Achieving Health for All : Primary Health Care in Action - Schleiff, Meike; Bishai, David (Book collections on Project MUSE., 2020)
"This edited volume examines countries around the world that took seriously the Alma-Ata Declaration of 1978 and expanded their primary health care system for access by all citizens. This book makes a case for promoting population-level health through universal primary care"--